A Psychological Survey of Prem Chand’s Famous Short Story, Kafan (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Munshi Prem Chand is a well known fiction writer in Hindi language. Famous writings of this versatile genius have been translated into various languages all over the world. His short story, Kafan has been debated, discussed and analysed in manifold ways. It was and has been very difficult for the traditional moralists and even modern humanists to believe that a great writer like Prem Chand narrated the episode of the husband and the father-in-law of a deceased poor lady with their callousness carouse and pass the time of rapture in Epicurean felicity with the money ex-gratia collected for the Kafan (Shroud) for the dead body of that poor lady. Only psychological implications of what Madhav and Ghishu have thought and acted under their impulses can explain the meaning of Prem Chand’s narration in the words which appear to some extent unacceptable to moralists and humanists.